The death and emotions of nurses - prelude report - Nyklewicz, Wojciech; Krajewska-Kułak, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. Of the clinical nursing supervision shows that nurses feel difficult emotion towards death of patients and have not to cope with stress skills, therefore we examined of this phenomenon. Aim. An aim of examination was evaluation of the anxiety and depressions towards the death and evaluation styles to cope negative emotions and stress, when patients die. Material and methods. Examined were 100 of nurses, at present of students of graduate’s supplementary studies. All persons were professionally active. In examination used evaluation feeling towards the death author’s scale and used of standardized questionnaires: STAI, CISS, CECS and GHQ-12. Results and conclusions. Most of all examined nurses (74%) experience the very strong anxiety towards the death. Only 1/5 of persons use effective, the exercise concentrated style to cope the stress, instead 78% of nurses react ineffectively on the stress. Most of all of nurses uses the suppression the anger (69% of persons), suppression the depression (72%) and suppression the anxiety (76%). Nearly the half of nurses (39%) has disturbances of the health which need the therapy.